Specific Characteristics of Patriotic Education of Youth in Public Pedagogics - Orazimbetov Yermekbay Keulimjaevich (Web of Journals Publishing, 2023)
This article describes the unique features of epics, fairy tales, proverbs, folk songs and folk songs based on Karakalpak folk pedagogy.
Keywords: Karakalpak folk pedagogy, patriotism, homeland, epics, tales, proverbs, folk songs and songs.